Altered splicing associated with the pathology of inflammatory bowel disease - Kiera Berger; Hari Somineni; Jarod Prince; Subra Kugathasan; Greg Gibson (Human Genomics, 2021)
Abstract Background Aberrant splicing of individual genes is a well-known mechanism promoting pathology for a wide range of conditions, but disease is less commonly attributed to global disruption of exon usage. To explore the possible association of aberrant splicing with inflammatory bowel disease, we developed a pipeline for quantifying transcript abundance and exon inclusion transcriptome-wide and applied it to a dataset of ileal and rectal biopsies, both obtained in duplicate from 34 pediatric or young adult cases of ulcerative colitis and Crohn’s disease. Results Expression and splicing covary to some extent, and eight individuals exhibited aberrant profiles that can be explained by altered ratios of epithelial to stromal and immune cells. Ancestry-related biases in alternative splicing accounting for 5% of the variance were also observed, in part also related to cell-type proportions. In addition, two individuals were identified who had 284 exons with significantly divergent percent spliced in exons, including in the established IBD risk gene CEACAM1, which caused their ileal samples to resemble the rectum. Conclusions These results imply that quantitative differences in splice usage contribute to the pathology of inflammatory bowel disease in a previously unrecognized manner.